Investigating the relationship between electricity consumption and economic growth: Evidence from South Africa. (December 2017) - Bah, Muhammad Maladoh; Azam, Muhammad
Abstract: This paper explores the causal relationship among electricity consumption, economic growth, financial development and CO2 emissions for South Africa over the period 1971–2012. The Autoregressive Distributed Lag (ARDL) bounds test is used to test for the presence of cointegration, whereas the Toda and Yamamoto augmented Granger causality test is used for direction of causality. The results of ARDL-bounds test validate the existence of cointegration among the included variables. Further, the Toda and Yamamoto Granger causality test affirms that there is no causality between electricity consumption and economic growth. This signifies that neutrality hypothesis holds for South Africa during the period under the study. Additionally, there is a unidirectional causality running from CO2 emissions to electricity consumption as well as a unidirectional causality running from financial development to CO2 emissions. The empirical finding suggests that policy-makers should establish concrete plans to increase investment in the electricity sector to ensure reliability of supply. Moreover, policy-makers need to address the pressing environmental concern by tapping into the sizeable renewable energy potential of the country. Consequently, it will assist in promoting sustainable economic growth and development.